Hydrogen sulfide impacts on inflammation-induced adipocyte dysfunction. (September 2019) - Comas, Ferran; Latorre, Jèssica; Cussó, Olaf; Ortega, Francisco; Lluch, Aina; Sabater, Mònica; Castells-Nobau, Anna; Ricart, Wifredo; Ribas, Xavier; Costas, Miquel; Fernández-Real, José Manuel; Moreno-Navarrete, José María
Abstract: A dual role of hydrogen sulfide (H2 S) in inflammation is well-reported and recent studies demonstrated adipogenic effects of H2 S in 3T3-L1 cells. Here, we aimed to investigate the effects of H2 S on adipocyte differentiation and inflammation. H2 S concentration in 3T3-L1 culture media was increased during adipocyte differentiation in parallel to adipogenic and Cth gene expression, and its inhibition using DL-Propargyl Glycine (PPG) impaired 3T3-L1 differentiation. GYY4137 and Na2 S administration only in the first or in the last stage of adipocyte differentiation resulted in a significant increased expression of adipogenic genes. However, when GYY4137 or Na2 S were administrated during all process no significant effects on adipogenic gene expression were found, suggesting that excessive H2 S administration might exert negative effects on adipogenesis. In fact, continuous addition of Na2 S, which resulted in Na2 S excess, inhibited adipogenesis, whereas time-expired Na2 S had no effect. In inflammatory conditions, GYY4137, but not Na2 S, administration attenuated the negative effects of inflammation on adipogenesis and insulin signaling-related gene expression during adipocyte differentiation. In inflamed adipocytes, Na2 S administration enhanced the negative effects of inflammatory process. Altogether these data showed that slow-releasing H2 S improved adipocyte differentiation in inflammatory conditions, and that H2 S proadipogenic effects depend on dose, donor and exposure time. Highlights: H2 S releasing donors administration in the first or in the last stage of adipocyte differentiation has adipogenic effects. H2 S excess administration inhibited adipocyte differentiation. Administration of a slow-releasing H2 S donor attenuated the negative effects of inflammation on adipogenesis.